Fiber Type-Specific Proteomic Alterations in R349P Desminopathy Mice - Eggers, Britta; Schork, Karin; Turewicz, Michael; Barkovits, Katalin; Eisenacher, Martin; Schröder, Rolf; Clemen, Christoph Stephan; Marcus, Katrin (Muscle & Nerve, 2025)
Introduction/Aims: Desminopathies are a group of rare human myopathies and cardiomyopathies caused by pathogenic variants of the desmin gene. Here, we analyzed the effects of the R349P mutant desmin on the proteomic profiles of individual fiber types of murine skeletal muscle. Methods: Soleus and tibialis anterior muscles from hetero- and homozygous R349P desmin knock-in mice and wild-type siblings were used to collect fiber type-specific material by laser microdissection to determine their proteomic profiles. Results: Aberrant proteomic profiles were observed in all four fiber types of homozygous mice. Type I and IIa fibers from homozygous muscle showed an increased abundance of 15 fibrotic proteins, for example, collagens I, IV, and VI, and associated proteins. Filamin-C, xin actin-binding repeat-containing proteins 1 and 2, and Kelch-like protein 41 were more abundant in homozygous fibers. A high number of proteins associated with the mitochondrial complexes had markedly lower amounts in all types of homozygous and type IIb heterozygous fibers, whereby 20 proteins of complex I, 6 proteins of complex III, 7 proteins of complex IV, and 4 proteins of complex V were found to be decreased in homozygous mice in at least one fiber type. This reduction included all mtDNA-encoded proteins of complexes I and V, as well as ADP/ATP translocase 1 and 2. Discussion: Our proteomic findings highlight a more severe myodegenerative process in fibers derived from homozygous R349P desmin knock-in mice. R349P desmin altered the abundance of proteins of the sarcomeric and extrasarcomeric cytoskeleton, extracellular matrix, and mitochondrial energy metabolism.
CRIS-Team Scopus Importer:2025-03-21
Keywords: desminopathy; fiber types; laser microdissection; proteomics; skeletal muscle